Áburðargjöf í lífrænni ræktun á Íslandi - Stadler, Christina Maria 1975- (2014)
Rit LbhÍ nr. 48 In the past, organic vegetable crops in Iceland were fertilised mainly with mushroom compost (1,9% N). However, due to the contamination with conventional chicken manure this fertiliser is to be replaced. Thus, substitutes are urgently needed. Plant compost (0,9% N), composted animal residues (1,9-2,6% N), clover (3,56% N), residues from the fish industry (10,9% N), grain legumes (4,3% N) and commercial organic fertilisers (216 mg N/l) have been tested in a pot experiment with perennial ryegrass (Lolium perenne L.). Fertilisers (800 mg N) were mixed into different greenhouse soils and dry matter yield was observed and plant N utilisation over the time investigated. A selection of the above mentioned organic fertilisers was tested in a basil (variety ‘Genoveser’) experiment and in a greenhouse experiment with sweet pepper (variety ‘Ferrari’) and tomatoes (variety ‘Encore’). Plants were grown with a plant distance in the row of 49,25 / 48,25 cm (tomatoes / sweet pepper), 2,5 / 3,3 plants/m² (tomatoes / sweet pepper with 2 tops/plant) and 200 kg N/ha fertiliser was applied in a split application within a fertiliser band of 30 cm during a growth period of seven months. The yield of tomatoes and sweet pepper was measured and soil samples regularly taken and analysed for nitrate-N. A fertiliser application resulted in comparison to the unfertilised control in a higher DM yield. The yield increase was higher with fertilisers with a high N content. The composted animal residues were comparable to mushroom compost. The time course of the apparent N utilisation of ryegrass differed strongly depending on the organic fertiliser used. The cumulative fertiliser-N uptake of ryegrass was highest for Pioner complete 6-1-3®, fishmeal and clover. A medium apparent N utilisation of ryegrass (40-50%) was achieved for chicken compost and fababean. The cumulative fertiliser-N uptake was lowest for plant, sheep, cow and horse compost as well as for the reference fertiliser mushroom compost. Different soils also had an ...